Role of polymorphisms TNF.- alpha gene in the development of recurrent miscarriage after in vitro fertilization in the residentS of Odessa region of Ukraine - Golovatyuk, K. P. (Journal of Education, Health and Sport, 2017)
Golovatyuk K. P. Role of polymorphisms TNF.- alpha gene in the development of recurrent miscarriage after in vitro fertilization in the residentS of Odessa region of Ukraine. Journal of Education, Health and Sport. 2017;7(1):323 - 332. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.265805 http://ojs.ukw.edu.pl/index.php/johs/article/view/4218 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. UDK 618.177-089.888.11:618.39-0796:575.162 ROLE OF POLYMORPHISMS TNF- alpha GENE IN THE DEVELOPMENT OF recurrent miscarriage after in vitro fertilization in THE residentS of Odessa region of Ukraine K. P. Golovatyuk Odessa National medical University, Ukraine; nosenko.olena@gmail.com; info@gameta.od.ua Summary The frequency of genotypes and allelic variants of the TNF-α gene (-238 G> A, -308 G> A, -1031 T > C), depending on the reproductive status and evaluation of its association with recurrent miscarriage (RM) in cycles in vitro fertilization (IVF) has been studied. The residents of the Odessaregion of Ukrainehave been under examination. It has been revealed that typing of SNPs of genes of the immune response TNF-α (rs1799964) and TNF-α (rs1800629) may be used as an early diagnostic method and pregravida prediction of reproductive losses in infertile women with RM after IVF. Genotypes AA -308G> A, (GA + AA) -308G> A and TC-1031C, (TC + CC) -1031C TNF-α gene were statistically significant associated with an increased risk of RM after IVF. Key words: recurrent miscarriage, in vitro fertilization, tumor necrosis factor-α r, inheritance, polymorphism, genotype, polymerase chain reaction.